2016
DOI: 10.3390/ijms17081235
|View full text |Cite
|
Sign up to set email alerts
|

Biological Effect of a Hybrid Anticancer Agent Based on Kinase and Histone Deacetylase Inhibitors on Triple-Negative (MDA-MB231) Breast Cancer Cells

Abstract: We examined the effects of the histone deacetylase inhibitor (HDACi) suberoylanilide hydroxamic acid (SAHA) combined with the vascular endothelial growth factor receptor-1/2 inhibitor (3Z)-5-hydroxy-3-(1H-pyrrol-2-ylmethylidene)-2,3-dihydro-1H-indol-2-one on MDA-MB-231 breast cancer cells (triple-negative) in the form of both a cocktail of the separate compounds and a chemically synthesized hybrid (N-hydroxy-N'-[(3Z)-2-oxo-3-(1H-pyrrol-2-ylmethylidene)-2,3-dihydro-1H-indol-5-yl]octanediamide). Comparative flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…An important fact was that cell death was induced by both autophagy and apoptosis (69). These results were confirmed by Zhang et al, who used SAHA and the antiangiogenic kinase inhibitor Sorafenib in epithelial tumor cell types and found that this treatment suppressed the expression of anti-apoptotic proteins and increased the activation of CD95 extrinsic apoptotic and lysosomal protease pathways.…”
Section: Hdac Inhibitors As Anti-cancer Agentssupporting
confidence: 74%
See 1 more Smart Citation
“…An important fact was that cell death was induced by both autophagy and apoptosis (69). These results were confirmed by Zhang et al, who used SAHA and the antiangiogenic kinase inhibitor Sorafenib in epithelial tumor cell types and found that this treatment suppressed the expression of anti-apoptotic proteins and increased the activation of CD95 extrinsic apoptotic and lysosomal protease pathways.…”
Section: Hdac Inhibitors As Anti-cancer Agentssupporting
confidence: 74%
“…Nevertheless, the majority of studies in the field of TNBC therapy tend to combine HDAC inhibitors with kinase inhibitors, autophagy inhibitors, antibiotics, chemotherapy, IR, or even two HDAC inhibitors treatment in order to enhance their efficacy against TNBC (47,69,71,84,115,123,153). In the majority of the studies, co-treatment of an HDAC inhibitor with another compound induced the inhibition of tumor growth and showed anti-proliferative effects (46,47,77,84,115,123,138,154).…”
Section: Resultsmentioning
confidence: 99%
“…MDA-MB231 cells are endowed with a constitutively elevated autophagy rate. Inhibition of autophagy was proven to render them susceptible to the lethal effect of chemicals in various experimental conditions (e.g., [18,19,31,32]); on the other hand, lethal effects on this cell line induced by several autophagy inducers have been reported in the literature (e.g., [33,34]).…”
Section: Discussionmentioning
confidence: 99%
“…The goodness of hit score (GH) of this screening protocol was calculated to be 0.796 which indicates the significance of selected pharmacophore to identify active molecules. Further, an external dataset comprising of the known HDAC inhibitors (Librizzi et al, 2016; Patel et al, 2016; Wen et al, 2016; Zhu et al, 2016) that were not included in QSAR model generation and were used as external test set were selected for validating the predictive power of the developed QSAR model. The robustness of the developed QSAR model was analyzed by performing “Y-randomization” test, the low value of Rscramble2 (0.629) as compared to Rtrain2 of selected model, described the real regression correlation of the selected model.…”
Section: Resultsmentioning
confidence: 99%